Bilateral Serous Retinal Detachment as an Initial Manifestation of Systemic Lupus Erythematosus due to Hypoalbuminemia: A Case Report - Zikang Xu; Anyi Liang; Dan Cao; Liang Zhang (Case Reports in Ophthalmology)
Introduction: There are diverse etiologies of serous retinal detachment (SRD), and hypoalbuminemia is one of the rare causes of it. We report a case of bilateral SRD attributed to decreased serum albumin level caused by systemic lupus erythematosus (SLE). Case Presentation: A 28-year-old female with no significant past medical history presented with bilateral palpebral edema for 10 days and blurred vision for 3 days. Optical coherence tomography demonstrated subretinal fluid in both eyes; fluorescein angiography revealed multiple hyperfluorescent spots with late leakage and pooling. Extensive serological and systemic examinations showed a slight decrease in serum albumin level with no other notable abnormalities. With the suspected diagnosis of Vogt-Koyanagi-Harada disease, the patient received high-dose intravenous corticosteroid therapy without any improvement. However, significant clinical improvement was achieved after albumin supplementation and corticosteroid dose tapering. The decrease in albumin levels in this patient was ultimately found to be due to protein-losing enteropathy (PLE) caused by SLE. Conclusions: This case presented a rare cause of bilateral SRD associated with hypoalbuminemia induced by SLE-related PLE. The report revealed that ocular involvements such as palpebral edema and SRD can be the initial manifestations of SLE rather than common lupus retinopathy. It emphasized the values of ocular manifestations as a clue for prompt diagnosis and management of systemic conditions.